2021
DOI: 10.1039/d1cb00169h
|View full text |Cite
|
Sign up to set email alerts
|

An overview of methods for the structural and functional mapping of epitopes recognized by anti-SARS-CoV-2 antibodies

Abstract: This mini-review presents a critical survey of techniques used for epitope mapping on the SARS-CoV-2 Spike protein. The sequence and structures for common neutralizing and non-neutralizing epitopes on the Spike...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…The region identified here as the binding epitope matches that found by both Yuan et al [47] and Wu et al [48]. The binding site mapped to the complete trimer of the SARS-CoV-2 spike protein, shown in Figure 4F, showed that the binding site is located on the tip of the receptor-binding domain and is accessible in both closed and open structure [49].…”
Section: Discussionsupporting
confidence: 83%
“…The region identified here as the binding epitope matches that found by both Yuan et al [47] and Wu et al [48]. The binding site mapped to the complete trimer of the SARS-CoV-2 spike protein, shown in Figure 4F, showed that the binding site is located on the tip of the receptor-binding domain and is accessible in both closed and open structure [49].…”
Section: Discussionsupporting
confidence: 83%
“…Hydrogen–deuterium exchange coupled with mass spectrometry (HDX–MS) is a method often used for antibody epitope mapping. Recent examples include the use of HDX–MS to augment electron microscopy data for mapping the binding sites for a panel of monoclonal antibodies (mAbs) in the work that led to the discovery of LY-CoV555, and for the screening of receptor-binding domain (RBD) epitopes in the development of the REGEN-COV mAb cocktail . In a typical HDX–MS experiment, the protein of interest is incubated in a D 2 O buffer, allowing the hydrogens to exchange with deuterium for set time periods.…”
mentioning
confidence: 99%
“…Most of the current methods for diagnosing allergenic proteins predominantly rely on the accurate mapping of IgE epitopes, which requires detailed peptide analysis [30], or high-resolution techniques [31], such as the 3D structure of an Antigen-Antibody complex solved by X-ray crystallography. Existing allergen prediction methods are limited by their reliance on relatively small datasets that contain, at most, a few hundred proteins, with a high degree of redundancy [17].…”
Section: Discussionmentioning
confidence: 99%